Bacterial and fungal penetration of the Nile crocodile (Crocodylus niloticus) egg in relation to the eggshell and eggshell membrane anatomy and microstructure - Myburgh, Jan G. (University of Pretoria, 2023)
Thesis (PhD)--University of Pretoria, 2023.